Mental Health of Children With Attention Deficit and Hyperactivity Disorder and Their Parents During the COVID-19 Lockdown: A National Cross-Sectional Study - Bobo, E.; Fongaro, E.; Lin, L.; Gétin, C.; Gamon, L.; Picot, M-C.; Purper-Ouakil, D. (Frontiers in Psychiatry, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has caused a real disruption of children’s lives. Children with neurodevelopmental disorders and their parents seem to be particularly vulnerable to adverse mental health effects due to lockdown policies. This study explores the psychological state of children with Attention Deficit Hyperactivity Disorder (ADHD) and their parents during the first lockdown in France. A national prospective cross-sectional parent-reported study was conducted using an online survey disseminated through different social networks of French ADHD associations during the first lockdown. The survey consisted of open-ended, multiple choice questions and standardized questionnaires such as the Strengths and Difficulties Questionnaire (SDQ), the coping self-report questionnaire (Brief COPE) and the Patient Health Questionnaire-2 (PHQ-2). A total of 538 parents completed the online survey between the 6th and the 15th of April 2020. These results suggest that most children (65.29%) did not experience a worsening of their behavior but still had pathological levels of hyperactivity (56.47%) and behavioral (57.60%) symptoms at the time of the first lockdown. In addition, some parents (26.27%) showed responses indicating possible major depressive disorder. Positive parental coping strategies were associated with both improved child behavior and fewer parental depressive symptoms. Strengthening parents’ coping strategies may be an effective intervention to protect both parents and children with ADHD from the negative psychological effects of lockdown. In times of pandemic, psychological care modalities must evolve to provide quality online interventions for families of children with ADHD.